Large-scale Monte Carlo neutron transport calculations with thermal hydraulic feedback. (October 2015) - Ivanov, A.; Sanchez, V.; Stieglitz, R.; Ivanov, K.
Highlights: Method of internal coupling, based on dynamic material distribution, is presented. The Wielandt shift method is implemented to accelerate Mote Carlo calculations. The Uniform Fission Site method is introduced for tallies with large numbers of bins. The stochastic approximation scheme is used to stabilize coupled code convergence. Abstract: The Monte Carlo method provides the most accurate description of the particle transport problem. The criticality problem is simulated by following the histories of individual particles without approximating the energy, angle or the coordinate dependence. These calculations are usually done using homogeneous thermal hydraulic conditions. This is a very crude approximation in the general case. In this paper, the method of internal coupling between neutron transport and thermal hydraulics is presented. The method is based on dynamic material distribution, where coordinate dependent temperature and density information is supplied on the fly during the transport calculation. This method does not suffer from the deficiencies characteristic of the external coupling via the input files. In latter case, the geometry is split into multiple cells having distinct temperatures and densities to supply the feedback. The possibility to efficiently simulate large scale geometries at pin-by-pin and subchannel level resolution was investigated. The Wielandt shift method for reducing the dominance ratio of the system and accelerating the fission source convergence was implemented. During the coupled iteration a detailed distribution of the fission heat deposition is required by the thermal hydraulics calculation. Providing reasonable statistical uncertainties for tallies having large numbers of bins, is a complicated task. This problem was resolved by applying the Uniform Fission Site method. Previous investigations showed that the convergence of the coupled neutron transport/thermal hydraulics calculation is limited by the statistical uncertainty and exhibits strong nonuniform behavior. The stochastic approximation scheme was used to stabilize the convergence. In combination with the Uniform Fission Site method, uniform convergence was achieved.